2015
DOI: 10.1063/1.4927237
|View full text |Cite
|
Sign up to set email alerts
|

Frictional effects near a metal surface

Abstract: When a classical master equation (CME) is used to describe the nonadiabatic dynamics of a molecule at metal surfaces, we show that in the regime of reasonably strong molecule-metal couplings, the CME can be reduced to a Fokker-Planck equation with an explicit form of electronic friction. For a single metal substrate at thermal equilibrium, the electronic friction and random force satisfy the fluctuation-dissipation theorem. When we investigate the time scale for an electron transfer (ET) event between the mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(93 citation statements)
references
References 28 publications
6
86
1
Order By: Relevance
“…Several other research groups have also identified the same effective friction tensor [28] using different methodologies, some using influence functionals [29] and some using non-equilibrium Green's functions (NEGF) [30,31]. The effects of non-Condon terms have also been considered [32][33][34] at finite temperature.…”
mentioning
confidence: 99%
“…Several other research groups have also identified the same effective friction tensor [28] using different methodologies, some using influence functionals [29] and some using non-equilibrium Green's functions (NEGF) [30,31]. The effects of non-Condon terms have also been considered [32][33][34] at finite temperature.…”
mentioning
confidence: 99%
“…where we follow the notation of [5]:d andd † are the annihilation and creation operators for the two-level electron state of the molecule,ĉ k andĉ † k are the annihilation and creation operators for electron states in the bath, E k is the energy level of those states, µ is the Fermi level, and V k is the coupling strength between the molecule and the k-th mode in bath, assumed to be real. The Hilbert space corresponds to the molecule is thus L 2 (R) ⊗ C 2 = L 2 (R) ⊗ span |0〉, |1〉 , so that we haved |1〉 = |0〉 andd † |0〉 = |1〉.…”
Section: Anderson-holstein Modelmentioning
confidence: 99%
“…In the first part, we attempt to justify the formal derivation of [5] in a more mathematical way. In the second part, more importantly, we attempt to study the phase space counterparts of Lindblad equation by applying Wigner transformation.…”
Section: Semi-classical Limitmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there has been no conclusion in the literature as to the differences between these friction tensors. For instance, on the one hand, are there perhaps different forms for electronic friction, just as there are many slightly different master equations 53,[63][64][65][66][67] ? When studying rate crossings near a metal surface, Hynes el al derived a non-Markovian friction tensor and argued that this friction tensor was "quite distinct [from the HGT] Markovian electronic friction, acting on a particle impinging from the gas phase on a metallic surface."…”
Section: Introductionmentioning
confidence: 99%